USP52 acts as a deubiquitinase and promotes histone chaperone ASF1A stabilization - Yang, Shangda (Nat Commun, 2018)
Histone chaperone ASF1A has been reported to be dysregulated in multiple tumors; however, the underlying molecular mechanism that how the abundance and function of ASF1A are regulated remains unclear. Here we report that ASF1A is physically associated with USP52, which is previously identified as a pseudo-deubiquitinase. Interestingly, we demonstrate that USP52 is a bona fide ubiquitin-specific protease, and USP52 promotes ASF1A deubiquitination and stabilization. USP52-promoted ASF1A stabilization facilitates chromatin assembly and favors cell cycle progression. Additionally, we find that USP52 is overexpressed in breast carcinomas, and its level of expression correlates with that of ASF1A. Moreover, we reveal that impairment of USP52-promoted ASF1A stabilization results in growth arrest of breast cancer cells and sensitizes these cells to DNA damage. Our experiments identify USP52 as a truly protein deubiquitinase, uncover a molecular mechanism of USP52 in chromatin assembly, and reveal a potential role of USP52 in breast carcinogenesis.